2022
DOI: 10.3390/polym14224858
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Mechanical Properties of Concrete Incorporating Silica Fume and Waste Rubber Powder

Abstract: Using waste rubber tires for concrete production will reduce the demand for natural aggregate and help to reduce environmental pollution. The main challenge of using waste rubber tires in concrete is the deterioration of mechanical properties, due to poor bonding between rubber and cement matrix. This research aims to evaluate the mechanical and thermal properties of rubberised concrete produced by using different proportions of rubber powder and silica fume. Ordinary Portland cement was partially replaced wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 87 publications
0
10
0
2
Order By: Relevance
“…Similarly, the tensile strength of the concrete also showed a similar trend of strength improvement when tire aggregates were treated with the different solvents discussed here [28]. The researchers also used tire aggregate in powder form [29,30] to replace the natural fine aggregate in concrete. Like coarse tire aggregate, concrete strengths were also reduced as the percentages of tire powder content increased in the mixes.…”
Section: Introductionmentioning
confidence: 64%
“…Similarly, the tensile strength of the concrete also showed a similar trend of strength improvement when tire aggregates were treated with the different solvents discussed here [28]. The researchers also used tire aggregate in powder form [29,30] to replace the natural fine aggregate in concrete. Like coarse tire aggregate, concrete strengths were also reduced as the percentages of tire powder content increased in the mixes.…”
Section: Introductionmentioning
confidence: 64%
“…The other explanation could be in relation to the generally smooth surface of polymeric materials. To improve the bonding of the cement matrix with the surface of the thermoplastic material, the application of supplementary cementitious materials, such as silica nanoparticles or fly ash, constitutes a promising approach [67,68]. Because of the reduced water transport capability of the produced W-A composites, it is expected that EPS bead-dosed concrete will be more durable against corrosion and chemical attack (like the penetration of salt solutions from winter roads and pavement maintenance [51]) than traditional dense aggregate-filled composites [13].…”
Section: Microscopic Observationmentioning
confidence: 99%
“…The other explanation could be in relation to the generally smooth surface of polymeric materials. To improve the bonding of the cement matrix with the surface of the thermoplastic material, the application of supplementary cementitious materials, such as silica nanoparticles or fly ash, constitutes a promising approach [67,68].…”
Section: Microscopic Observationmentioning
confidence: 99%
“…CRC is a composite based on ordinary concrete that is formed by adding finer crumb rubber to replace some of the fine aggregate or larger crumb rubber to replace some of the coarse aggregate. Research has shown that CRC outperforms ordinary concrete in terms of energy absorption and consumption [ 13 , 14 ], fatigue resistance [ 15 ], reducing material brittle failure [ 16 ], deformation capacity [ 17 ], hindering crack development [ 18 ], durability [ 19 , 20 , 21 ], and thermal performance [ 22 ]. To reduce the degree of brittle failure of deep foundation pit support structures, the application of CRC to deep foundation pit support has been studied [ 16 ].…”
Section: Introductionmentioning
confidence: 99%